Phlegmasia cerulea dolens as a complication of radiation therapy in endometrial cancer: a case report - Milan Ho, BS; Arash Fereydooni, MD, MS, MHS; Graeme McFarland, MD; Babak Litkouhi, MD; Amer Karam, MD; Edmund J. Harris, Jr, MD; Elizabeth L. George, MD, MS (AJOG Global Reports)
This study reports the case of a 61-year-old female patient with recurrent endometrial cancer who developed phlegmasia cerulea dolens and compartment syndrome of the right lower extremity 1 day after receiving high-dose radiation therapy. In addition, the patient had a right main pulmonary artery embolus. The patient underwent inferior vena cava filter placement, open common femoral vein thrombectomy, 4-compartment fasciotomy, and vacuum-assisted superficial groin wound closure. The patient was discharged on postoperative day 6 on rivaroxaban. Imaging at 6 months and 1 year postoperatively demonstrated a wide patency of the deep venous system in the right lower extremity, and anticoagulation was discontinued. The patient was followed up for surveillance in a gynecologic oncology clinic with no evidence of disease for 2 years, after which the patient was transferred to an outside facility. In conclusion, phlegmasia cerulea dolens can occur in the setting of immobility because of high-dose radiation therapy and in the absence of deep venous thrombosis prophylaxis. Rapid identification of phlegmasia cerulea dolens on physical examination and early vascular surgical intervention can result in favorable outcomes.